Desenvolvimento inicial de jurema branca em diferentes tipos e usos do solo da caatinga - Gomes, Luiz Henrique dos Santos (2015)
The Caatinga has different soil types, forming a heterogeneous mosaic. This is due to environmental variability in the areas of biome, particularly with regard to geological materials soil formation, topography and climate change. Thus, there are different types of soils therefore occur various uses thereof. The introduction of trees in production systems, you should choose species adapted to soil and climatic and topographic conditions of agricultural establishments. An endemic species of the biome and which is already being exploited in the region is the Jurema Branca (Piptadenia stipulacea). Producing species loggers and non-timber, which may turn out to generate income for the agricultural establishments. Due to varying soil types found in the Caatinga and its different uses, aimed to evaluate the initial growth, spontaneous nodulation of roots and production of dry biomass White Jurema, up to 90 days. They were taken collected from soils in areas identified with eutrophic Oxisol, eutrophic Cambisol and Planosol in areas with agricultural practices, the Caatinga native forest and degraded and / or degradation area, featuring land use. Later, it began an experiment to evaluate the Jurema Branca, in different types and land uses. The variables studied were the initial growth of the total height and diameter basis, spontaneous nodulation on roots and production of dry biomass of shoots, roots and the whole plant. Plants grown in the soil of agricultural practices, showed average for total height, base diameter, number of nodules and dry matter of the whole plant 63.8 cm, 3.9 mm, 15 nodules / plant, 17.7 g, respectively. The initial growth, spontaneous nodulation and the production of dry biomass Jurema Branca, were favored, in general, in soils with use of farming practices, regardless of the type of soil used in the kind of cultivation